2010
DOI: 10.1111/j.1439-0272.2009.00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Leucocytes and intrinsic ROS production may be factors compromising sperm chromatin condensation status

Abstract: Considering that the final protection of the DNA against major assaults in terms of chromatin condensation is finalized in the epididymis, it is not known how sperm production of reactive oxygen species (ROS) and inflammatory processes can contribute to protamine deficiency that is predetermined in the testes. Therefore, this study aimed at investigating relationships between poor chromatin condensation, morphology, ROS production, DNA damage and the impact of the presence of leucocytes. In 70 patients, sperm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 38 publications
1
32
1
Order By: Relevance
“…and increased ROS possibly render DNA more susceptible to damage [De Iuliis et al 2009]. Henkel et al [2010] have also obtained a positive association between ROS production and CMA3+ sperm. A significant correlation between the percentage of 8-OHdG-positive sperm with under protamination and reduced mitochondrial membrane potential has been reported [De Iuliis et al 2009].…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…and increased ROS possibly render DNA more susceptible to damage [De Iuliis et al 2009]. Henkel et al [2010] have also obtained a positive association between ROS production and CMA3+ sperm. A significant correlation between the percentage of 8-OHdG-positive sperm with under protamination and reduced mitochondrial membrane potential has been reported [De Iuliis et al 2009].…”
Section: Discussionmentioning
confidence: 81%
“…These results collectively suggest that as sperm undergo apoptosis, they become PI+. Henkel et al [2010] also assessed the relation between ROS production and DNA fragmentation using the TUNEL assay. Unlike the correlations observed between ROS production with apoptosis, they did not observe a correlation between ROS and DNA fragmentation [Henkel et al 2010].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although seminal leukocytes have the potential to cause oxidative stress, the intrinsic ROS production of spermatozoa themselves also leads to oxidative damage in male gametes, once it exceeds the ability of intrinsic sperm enzymatic and nonenzymatic systems to its neutralization [86,87]. Some investigators have reported stronger relationships between intrinsic than extrinsic ROS production in semen and sperm DNA integrity [49].…”
Section: Role Of Oxidative Stressmentioning
confidence: 99%